Deep eutectic solvent extraction and biological activity of polysaccharides from Tenebrio molitor - Shengru Yang; Xu Li; Qiaoli Li (Heliyon)
This study aimed to extract polysaccharides from Tenebrio molitor using ultrasound-assisted deep eutectic solvent (DESs) and to evaluate their structural features, as well as their antimicrobial, antioxidant, and α-amylase inhibitory activities. Various DESs were tested for polysaccharides extraction, and the process was optimized using response surface methodology (RSM). A preliminary structural analysis of the polysaccharides was conducted using infrared spectrum. The DESs were characterized by measuring their pH, viscosity, conductivity, refractive index, and density. The optimal extraction agent and parameters were determined. Significant differences in pH, viscosity, and conductivity were observed among DESs, whereas differences in refractive index and density were not significant. Choline chloride-lactic acid was identified as the optimal extraction agent. The optimal extraction parameters were a DES molar ratio of 1:2.1, a water content of 27 %, an extraction temperature of 70 °C, and an extraction time of 44 min, resulting in polysaccharides yield of 18.62 %. The extracted polysaccharides exhibited strong inhibitory effects against Salmonella, along with antioxidant activity and α-amylase inhibitory activities. The study demonstrated that polysaccharides from Tenebrio molitor can be efficiently extracted using DESs, showcasing significant biological activities, including antibacterial, antioxidant, and α-amylase inhibitory properties. These findings highlight the potential applications of Tenebrio molitor polysaccharides as valuable biological resources.